Bleeding Spitz nevus. - Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Hypopigmented or angioma-like Spitz nevus is not easily diagnosed (1, 3). It should be more frequently differentiated from eruptive lobular angioma -ELA- (2). The latter grows very rapid-ly so that gets eroded almost always and bleeds 4-6 weeks after its onset. The clinical features of hypopigmented Spitz nevus are due to the lack or scarcity of melanic pigment and to superficial telangiectases. It grows slowly as compared with ELA, reaches its maximum size within 6 months and does not bleed. When it is not removed, its natural history goes on towards the spontaneous regression or the pigmentation. In the case here reported, the clinical and dermoscopic features were not diagnostic. Only the histology led to the right diagnosis of Spitz nevus.